Molecular Phylogeography and Intraspecific Divergences in Siberian Wildrye (Elymus sibiricus L.) Wild Populations in China, Inferred From Chloroplast DNA Sequence and cpSSR Markers - Xiong, Yi; Xiong, Yanli; Shu, Xin; Yu, Qingqing; Lei, Xiong; Li, Daxu; Yan, Jiajun; Bai, Shiqie; Ma, Xiao (Frontiers in Plant Science, 2022)
The detailed understanding of the distribution and degree of genetic variation within a species is important for determining their evolutionary potential, which in return facilitates the development of efficient conservation strategies aimed at preserving adaptive genetic variation. As an important perennial, cool-season grass in temperate Eurasia, increasing attention has been paid to Siberian wildrye (Elymus sibiricus) due to its excellent ecological utilization value and forage production potential in China, especially in the Qinghai-Tibet Plateau (QTP) regions. In this study, we applied two chloroplast (cp) genes (matK and rbcL), three cp spacer regions (trnY-GUA~trnD-GUC, atpH~atpF and rps4~trnT-UGU), and six cpSSR markers to the genetic and phylogenetic analysis of 137 wild E. sibiricus accessions from 23 natural populations that represent the main distribution regions in China. The results show the highest genetic diversity (h = 0.913) and haplotype richness (10 haplotypes) for the QTP population, which indicates QTP as the probable diversity center and geographic origin of E. sibiricus in China. Population divergence was high, indicating a significant phylogeographic structure together with a significantly higher Nst value (Nst > Gst, P < 0.05) at the species level, QTP+XJ (combined populations from QTP and XinJiang), QTP+NC (combined populations from QTP and North China), and XJ+NC (combined populations from XinJiang and North China) group levels, respectively. An expansion was revealed in the distributional range of E. sibiricus in China from paleo times up to the recent past, while a dramatic range contraction was predicted for the near future. The predicted main limiting factor for further spread of E. sibiricus is an increasing global mean temperature. We recommend that the combination of Es-cpDNA1 and Es-cpDNA3+4+5 can be used as effective markers for phylogenetic analysis and phylogeographical history analysis of E. sibiricus. These findings shed new light on the historical population dynamics of cold-season herbs in the QTP region and the north of China, and is of great significance for the future establishment of protection and collection strategies for wild E. sibiricus germplasm.